Estimation of Flow in Horizontal Elliptic Channels with Free Overfall at the End of the Channel (University of Thi-Qar Journal for Engineering Sciences, 2011)
The aim of this work is to calculate the flow discharge in horizontal elliptic channels with free overfall at the end of the channel. Two methods are used, the first one is Boussinesq approximation to calculate the End- Depth – Ratio ( EDR ) .The second one is a theoretical procedure applied to compute the flow over a sharp – crested weir.The available experimental data are used to verify the proposed End – Depth – Discharge (EDD) relationship. The calculated discharges, using the proposed EDD relationship, show excellent agreement with the experimental values in subcritical flows. However, the agreement is not so good in supercritical.